A systematic review of delays in seeking medical attention after transient ischaemic attack. Issue 8 (8th March 2009) - Sprigg, N; Machili, C; Otter, M E; Wilson, A; Robinson, T G
Abstract : Background: Prompt assessment and investigation of transient ischaemic attack (TIA) followed by early initiation of secondary prevention is effective in reducing recurrent stroke. Nevertheless, many patients are slow to seek medical advice after TIA. A systematic review was undertaken to examine potential factors associated with delay in seeking medical review after TIA. Methods: The electronic databases MEDLINE, EMBASE, and Science Citation Index were searched for observational studies assessing patient delay in presentation after TIA. The search was restricted to studies published between December 1995 and September 2008. Results: The electronic search yielded nine studies with data on presentation delay in patients with TIA; variations existed in study size, population and methodology. One study included patients with TIA only (n = 241), whereas the remaining eight studies recruited both stroke and TIA patients. Overall, TIA patients (n = 821) made up only a small proportion of the total number of patients in this analysis (n = 3, 202). Length of delay varied greatly across all studies. In most studies, patients with TIA who attended an emergency department arrived there within hours. Where patients first presented to their general practitioner, 50% attended within 24 hours whereas 25% waited 2 days or more. Recognition of symptoms as stroke/TIA did not reduce the delay. Conclusions: The majority of delay in seeking assessment after TIA is due to a lack of response by the patient—many patients do not recognise the symptoms of stroke/TIA, and even when they do, many fail to seek emergency medical attention. The public needs educating on the importance of contacting the emergency medical services or attending an emergency department immediately after TIA.